Strategi Parenting dalam Mengembangkan Kepercayaan Diri dan Bakat Anak Usia Dini di PAUD Ash-Shadiqi Pondok Pesantren Miftahul Ulum Sumur Tengah - Titik Aisyah; Santi; Aisyah; Muhammad Mahmudi (STIT Al - Ibrohimy Bangkalan, 2025)
Parenting is one of the key factors that determines a child’s growth and development, particularly in the aspects of self-confidence and talent. Early childhood is considered the golden age of development, which requires optimal stimulation from both parents and educators. This community service program was carried out at PAUD Ash-Shadiqi, Pondok Pesantren Miftahul Ulum, Sumur Tengah, Pamekasan, with the aim of providing parenting strategies based on educational activities to develop children’s potential. The program utilized the momentum of Independence Day celebrations through various creative competitions (coloring, mother-child collaboration, rubber relay, balloon train, and art performances) involving children, teachers, and parents. The results showed that children became more confident to perform, more expressive in showcasing their talents, and developed a sense of sportsmanship. Parents also gained education on the importance of providing support, motivation, and guidance as part of positive parenting.